Gaya Kepemimpinan dan Pendekatan Spiritual Kepala Sekolah dalam Melakukan Blusukan di Sekolah Dasar Kota Lubuklinggau - Ahmad Gawdy Prananaosa; Tamri Tamri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to determine the influence of the school principal's leadership style and spiritual approach in conducting blusukan. This research uses a quantitative approach with multiple regression methods. The target population in this research is Lubuklinggau City elementary school principals, totaling 53 respondents. The sampling technique uses a stratified random sampling technique, namely, taking proportional random samples from each group in the school. As a result of the research, it was found that the correlation coefficient between the independent variable leadership style (X1) and the dependent variable blusukan (Y) or r x1y = 0.501, the coefficient of the principal's spiritual approach (X2) with the dependent variable blusukan performance (Y) or the correlation r x2y = 0.493 and The correlation coefficient between the leadership style variables (X1) and the principal's approach (X2) is r x1x2 = 0.429. Meanwhile, the r table value at the 5% significance level = 0.325 and the 1% significance level = 0.413. In conclusion, the influence of the independent variable leadership style (X1) and the independent variable principal's spiritual approach (X2) together with the blusukan variable (Y) is significant Keywords: Blusukan, Leadership Style, Spiritual Approach